Population pharmacokinetics and dose optimization of voriconazole in patients with COVID-19-associated pulmonary aspergillosis - Wang, Hui; Shen, Yue; Luo, Xuemei; Jin, Lu; Zhu, Huaijun; Wang, Jing (Frontiers in Pharmacology, 2025)
ObjectivesThe study aimed to investigate the pharmacokinetic profile of voriconazole in patients with COVID-19-associated pulmonary aspergillosis (CAPA) to optimize dosing strategies.MethodsPopulation pharmacokinetic modeling was conducted using clinical data from CAPA patients to analyze voriconazole’s pharmacokinetic behavior. A one-compartment model with first-order elimination was employed to characterize voriconazole disposition. Covariate analysis was further utilized to evaluate the impact of continuous renal replacement therapy (CRRT) and select biochemical markers on voriconazole clearance.ResultsThe model estimated voriconazole’s apparent clearance (CL/F) at 3.17 L/h and apparent volume of distribution (V/F) at 135 L for a standard patient with CAPA. Covariates such as CRRT, C-reactive protein, gamma-glutamyl transpeptidase, aspartate aminotransferase, and platelet count were found to significantly influence voriconazole clearance. Monte Carlo simulations indicated that patients on CRRT required both a higher loading dose and an increased maintenance dose compared to those not on CRRT.ConclusionThis study provides an evidence-based guide for voriconazole dosing adjustments in CAPA patients, particularly for those undergoing CRRT. The findings emphasize the importance of individualized dosing to improve therapeutic outcomes in this high-risk population.